“All this Regulatory Uncertainty in the Air”: The Indispensability of Public Hearings in Guarding and Guiding Public Deliberation - Carroll, Jaclyn; Bsumek, Pete (Frontiers in Communication, 2021)
The field of Environmental Communication has often critiqued the shortcomings of public hearings, noting their limitations in bringing about effective and equitable public decision making. While this work has been significant, it has tended to limit the deliberative field to public hearings themselves, sometimes going so far as to assume that public hearings are the only spaces in which significant deliberations occur. Using a field analysis of the “No Coal Plant” campaign in Surry County, Virginia (2008–2013), the authors illuminate some limitations of existing literature. Their analysis suggests that while public hearings can be extremely limiting, even “failed” public hearings can play a critical role in constituting, organizing, and pacing formal and informal deliberative spaces, which are necessary for communities as they manage the stresses and strains of the decision-making process.